Influence of atmospheric rivers on extreme precipitation in western Ukraine - Shchehlov, Oleksandr; Shpyg, Vitalii; Povshyk, Tetyana; Fomichev, Nikita (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2024)
Formulation of the problem. In recent years, interest in the atmospheric river (AR) phenomenon is growing, as more and more researchers associate it with extreme precipitation. Relatively few works are devoted to the assessment of the influence of atmospheric rivers on precipitation in Eastern Europe.The purpose of the article is to assess the occurrence of atmospheric river events during extreme precipitation in the western regions of Ukraine (Lviv and Volyn regions) and to analyze the geographical features of the spatial distribution of atmospheric river bends during extreme precipitation.Methods. We used the catalog of atmospheric rivers identified according to the methodology of D. Walliser and B. Guan to analyze the occurrence of atmospheric river events on the territory of the western part of Ukraine. Also, we used the sample of days with extreme precipitation (greater than 95th percentile for each meteorological station and each month) in the Lviv and Volyn oblasts of Ukraine to match it with AR episodes. It is shown that in most cases extreme precipitation events were accompanied by the atmospheric river phenomenon detected on the territory of Ukraine or the bordering territories.Results. The typical shape of atmospheric river bends during extreme precipitation most often is arc-shaped while the typical spatial coverage stretched from North Africa through the Mediterranean Sea and Turkey to the territory of Ukraine. Less often, the form of detected AR area had the form of a meridional bend extending from the eastern part of the Mediterranean Sea towards Ukraine. However, the analysis showed that the presence of atmospheric river phenomenon is not the exceptional reason for extreme precipitation. Part of the extreme precipitation events is associated with specific synoptic situations (precipitation caused by cold fronts or occluded fronts) whereas conditions for atmospheric river detection are not fulfilled (bend size, meridional flow component, flow intensity). Atmospheric river episodes were not observed at most of the days of general sample (on average 72.36%) within the study area based on the period of 1991-2020. At the same time, precipitation events in the absence of AR were recorded on average in 32.2% of days (relative to the total number of days). In the presence of AR, precipitation was not recorded in about a third of cases. In the sample of days in the absence of AR and in the presence of AR, the proportion of precipitation of different gradations is as follows: for 10-20 mm is 2.73% and 2.64% respectively; for 20-50 mm is 1.37% and 1.63%; more than 50 mm is 0 .19% against 0.16%. In the spring, there is a certain consistency with the negative daily value of the NAO index and the AR axis orientation from the southwest to the territory of Ukraine. Thus, within 5 days before the localization of AR on the territory of Ukraine, values of the NAO index <-0.5 are noted, but the index changes in the process of the pressure field change. Based on a limited sample of extreme precipitation (94 cases), we assessed the correspondence of the precipitation rate to the area of atmospheric rivers and their features of the spatial orientation. ARs extending from the southwest (north of Africa) and the south (western part of the Mediterranean Sea) are characterized by the greatest recurrence. No regularities were found either concerning the dependence of the precipitation rate on the orientation of the AR, or concerning the dependence of the number of stations with extreme precipitation on the orientation of the AR. No linear dependence was found for the area of atmospheric rivers within both the study region and the territory of Eastern and Southeastern Europe with daily precipitation in the western regions of Ukraine.